Ecotypes of triple-negative breast cancer in response to chemotherapy - Yun Yan; Yiyun Lin; Tapsi Kumar; Shanshan Bai; Aatish Thennavan; Jianzhuo Li; Emi Sei; Tuan Tran; Min Hu; Mitchell Rao; Chenling Tang; Siyuan He; et al. (Nature, 2026)
Abstract Triple-negative breast cancer (TNBC) is an aggressive subtype that is frequently treated with chemotherapy, but only half of the patients respond well and have good clinical outcome 1,2 . Here we leveraged pretreatment tissue samples from treatment-naive patients with TNBC who received neoadjuvant chemotherapy and performed single-cell transcriptomic analysis of 427,857 cells from 101 patients and spatial transcriptomic analysis of 44 patients. We classified TNBC tumours into 4 patient-level subtypes (archetypes) using the cancer-cell gene expression and identified 13 metaprograms that reflect intra-tumoural heterogeneity at the single-cell level. The TNBC tumour microenvironment consisted of 49 immune and stromal cell states, many of which were reprogrammed relative to normal breast tissues. Furthermore, we identified eight distinct cellular communities (ecotypes) on the basis of the co-occurrences of cancer cells and tumour microenvironment cell types, and their spatial organization in tissues. In contrast to previous studies on T cells, our data show the importance of macrophage subtypes and cancer-cell metaprograms for interferon signalling, human leukocyte antigen expression and cell cycle activity that are associated with a good response to neoadjuvant chemotherapy. Collectively, this study provides new insights into the biology of untreated TNBC tumours and their association with chemotherapy response.